2014
DOI: 10.18632/oncotarget.2391
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and erlotinib synergize to inhibit basal breast cancer

Abstract: Basal-like breast cancers (BBCs) are enriched for increased EGFR expression and decreased expression of PTEN. We found that treatment with metformin and erlotinib synergistically induced apoptosis in a subset of BBC cell lines. The drug combination led to enhanced reduction of EGFR, AKT, S6 and 4EBP1 phosphorylation, as well as prevented colony formation and inhibited mammosphere outgrowth. Our data with other compounds suggested that biguanides combined with EGFR inhibitors have the potential to outperform ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 57 publications
0
32
0
1
Order By: Relevance
“…MDA-MB-468, MDA-MB-157, MDA-MB-435S, MDA-MB-436, MDA-MB-231, MX-1, MCF7, BT20, L56Br-C1, CAOV-3, HCC1143, HCC1806, HCC1937, HCC1987, HCC70, HCC38, BT549, mice implanted with MDA-MB-468 cells into the mammary fat pad [186] Everolimus Metformin-induced additive effects were observed when used as a co-treatment with everolimus and inhibited cell proliferation and colony formation ability. The additive effect of the combinatorial treatment was also related to the inhibition of mitochondrial respiration and mTOR growth signaling.…”
Section: Mcf7/adr Cells-dox Resistant Cells Subcutaneouslymentioning
confidence: 99%
“…MDA-MB-468, MDA-MB-157, MDA-MB-435S, MDA-MB-436, MDA-MB-231, MX-1, MCF7, BT20, L56Br-C1, CAOV-3, HCC1143, HCC1806, HCC1937, HCC1987, HCC70, HCC38, BT549, mice implanted with MDA-MB-468 cells into the mammary fat pad [186] Everolimus Metformin-induced additive effects were observed when used as a co-treatment with everolimus and inhibited cell proliferation and colony formation ability. The additive effect of the combinatorial treatment was also related to the inhibition of mitochondrial respiration and mTOR growth signaling.…”
Section: Mcf7/adr Cells-dox Resistant Cells Subcutaneouslymentioning
confidence: 99%
“…At physiologic or low levels of glucose, the ability of metformin to inhibit cell proliferation and tumor formation, and induce apoptosis is optimized. 137,138 Metformin induces apoptosis of TNBC. Although not completely understood, metformin mediates this process by activating miR-193b, an inhibitor of fatty acid synthase, and AMP-activated protein kinase (AMPK), which inhibits signaling by mammalian target of rapamycin (mTOR) and signal transducer and activator of transcription-3 (STAT-3).…”
Section: Igf Axis and Triple-negative Breast Cancermentioning
confidence: 99%
“…Lau et al found that basal breast cancer responds well to metformin and erlotinib. 137 A combination of gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, and inhibition of activation of sphingosine kinase-1 (SphK1)/sphingosine 1-phosphate (S1P) system by IGFBP-3 prevented TNBC tumor growth. 148 To prevent metastasis, Mancini et al 79 investigated the efficacy of co-targeting IGF1 and IGF-2, and their receptors.…”
Section: Future Directions For Tnbc Treatmentmentioning
confidence: 99%
“…Metformin is available generically hypoglycaemic agents but also has been shown to play an efficient role against different types of cancer, alone or in combination with other drugs such as first‐generation EGFR‐TKIs . We recently reported that metformin‐based combinatorial therapy effectively blocked the growth of TKI‐resistant cancer cells via apoptosis induction and autophagy inhibition .…”
Section: Introductionmentioning
confidence: 99%